Métabolisme et adaptation : l’objectivation des phénomènes physiologiques et sensoriels nutritifs en psychiatrie (fin xixe-début xxe siècle) - Elsie Mégret (Socio-anthropologie)
At the intersection of the sociology of science and technology and the anthropology of the Living, this article explores how the measurement practices of physiological and sensory nutritional phenomena rely on a metric, energetic, and temporal understanding of the human being and its evolution. The article first analyzes the measurement practices of nutritional activity in hysterical patients conducted at the end of the 19th century by psychiatrists Constantin Empereur and Georges Gilles de La Tourette. It secondly examines the work of neurologists and psycho-physiologists Joanny Roux and Georges Noguès on the sensation of hunger and its pathological disappearance. The article suggests that while neurological psychiatry avoids a strictly mechanical approach to metabolism, psycho-physiological studies of hunger sensation reinforce a dynamic and adaptive reading of human nutrition, influenced by a Spencerian view of evolution.